Face perception in pure alexia: Complementary contributions of the left fusiform gyrus to facial identity and facial speech processing. (November 2017) - Albonico, Andrea; Barton, Jason J.S.
Abstract: Recent concepts of cerebral visual processing predict from overlapping patterns of face and word activation in cortex that left fusiform lesions will not only cause pure alexia but also lead to mild impairments of face processing. Our goal was to determine if alexic subjects had deficits in facial identity processing similar to those seen after right fusiform lesions, or complementary deficits affecting different aspects of face processing. We studied four alexic patients whose lesions involved the left fusiform gyrus and one prosopagnosic subject with a right fusiform lesion, on standard tests of face perception and recognition. We evaluated their ability first to process faces in linear contour images, and second to detect, discriminate, identify and integrate facial speech patterns into perception. We found that all five patients were impaired in face matching across viewpoint, but the alexic subjects performed worse with line-drawn faces, while the prosopagnosic subject did not. Alexic subjects could detect facial speech patterns but had trouble identifying them and did not integrate facial speech patterns with speech sounds, whereas identification and integration was intact in the prosopagnosic subject. We conclude that, in addition to their role in reading, the left-sided regions damaged in alexic subjects participate in the perception of facial identity but in a non-redundant fashion, focusing on the information in linear contours at higher spatial frequencies. In addition they have a dominant role in processing facial speech patterns, another visual aspect of language processing.